1997
DOI: 10.5089/9781451847826.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Euro, the Demand for Reserves, and Policy Coordination Under EMU

Abstract: The success of European Economic and Monetary Union (EMU) will depend on the stability of the euro. The monetary policy framework is yet to be decided, but is likely to involve either money or inflation targeting. Stochastic simulations compare the outcomes for major macroeconomic and financial variables pre-and post-EMU under both policy rules, as well as under an inflation targeting rule that includes output. Implications for the euro as a reserve currency are examined in the light of the expected returns an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
0
23
1
Order By: Relevance
“…In addition, when compared to the weights embodied in the SDR (using September 2005 exchange rates), the euro's optimal portfolio weight is 5 percentage points lower, sterling's 2 percent higher, and the yen's about equal, while the dollar's optimal share (43 percent) is 3 percent above its SDR weight (40 percent). The proportion for the euro is significantly below that calculated for the deutsche mark in Masson and Turtelboom (1997), despite a similar methodology. The reason is that in that study, the mean returns (calculated over 1981-95) on both deutsche mark and yen were considerably higher than dollar returns, and they were less variable as well.…”
Section:  Xmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, when compared to the weights embodied in the SDR (using September 2005 exchange rates), the euro's optimal portfolio weight is 5 percentage points lower, sterling's 2 percent higher, and the yen's about equal, while the dollar's optimal share (43 percent) is 3 percent above its SDR weight (40 percent). The proportion for the euro is significantly below that calculated for the deutsche mark in Masson and Turtelboom (1997), despite a similar methodology. The reason is that in that study, the mean returns (calculated over 1981-95) on both deutsche mark and yen were considerably higher than dollar returns, and they were less variable as well.…”
Section:  Xmentioning
confidence: 86%
“…This was the interpretation given in Masson and Turtelboom (1997), where a mean-variance model with historical returns were used to calculate optimal reserve holdings, in dollars, yen, and euros. In order to consider global reserve demand, returns were expressed in terms of the SDR, chosen as the numeraire.…”
Section: B) Currency Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of economists (e.g. Bergsten(1997Bergsten( , 1999, Masson and Turtelboom(1997), Portes and Rey(1998)) have suggested that exchange rate volatility between the dollar and the euro may well be higher than it was between the dollar and the German mark before 1999. The reasons are partly structural --euroland is much more self-contained than the individual countries were, so exchange rate variation will cause fewer internal disturbances, hence fewer calls for action to stabilize exchange rates; This greater volatility could be greatly aggravated if during the next decade foreign exchange holders around the world decide to switch their claims substantially from US dollar-denominated ones to euro-denominated ones, as some have suggested will occur (e.g.…”
Section: Rationale For the Proposalmentioning
confidence: 99%
“…This prediction derives from the constitution of the European Central Bank, which makes it more independent and more focused on price stability than the U.S. Federal Reserve. If anything, the constitution is even stricter than that of the Bundesbank, so that Europe's economy will be more stable than Germany's (Masson and Turtelboom, 1997). A counterargument is based on politico-economic considerations.…”
Section: Emu and The Rest Of The Worldmentioning
confidence: 99%